KONSEP ADIL DALAM POLIGAMI MENURUT HUKUM ISLAM - Supangat, Ajis (Ekonomi Syariah STAI Sangatta Kutai Timur, 2020)
We often discuss this theme in everyday life. Polygamy is a life phenomenon that occurs around us. The term polygamy is often heard, but not many people can accept this situation. In terms of fair means equating something with another in terms of size, so that something is impartial and does not differ from one another. The arrival of Islam with its polygamous verses, although it does not erase this practice, Islam limits the permissibility of polygamy to only four wives with strict conditions such as the obligation to be fair among wives. Whereas in Islamic law the scholars agree based on the strong argument that being fair to all wives is the obligation of a husband, as well as permitting polygamy, as in Surah An-Nisaa 'verse 3 and verse 129, justice that is conceived is justice that is materialistic that can control husbands who become his abilities, such as good treatment, sharing of time in the night and providing a living.